Treatment of Limbal Melanocytoma with Full Excision and a Fresh Homologous Corneoscleral Graft in a Dog - Tadeu Pigatto, João Antônio; de Albuquerque, Luciane; Marchionatti Pigatto, Anita; Fernandez da Silva, Alessandra; Torikachvili, Marcela; Borges de Vargas, Eduarda Valim; Driemeier, David (Acta Scientiae Veterinariae, 2020)
Background: Limbal melanoma has been diagnosed in dogs and due to progression may cause vision loss and eyeball removal. Definitive diagnosis is made through histopathological examination. Therapeutic options include full thickness resection and repair by homologous corneal tissue, synthetic graft material, and enucleation. In this report, we describe a case of limbal melanocitoma in a dog that has been treated successfully with fresh homologous corneoscleral graft.Case: A 5-year-old female Labrador was referred to the Ophthalmology Veterinary Section of the Federal University of Rio Grande do Sul (UFRGS), Porto Alegre, Brazil, with a history of a pigmented mass located on the left eye. Ophthalmic examination revealed a pigmented mass located at the left temporal limbus with corneal involvement. Surgical excision followed by reconstruction using fresh homologous corneoscleral was recommended. The patient was premedicated with acepromazine (0.05 mg/kg, IM) and meperidine (20 mg/kg, IM). Anaesthesia was induced with propofol (10 mg/kg, IV) and maintained with isoflurane. Atracurium (0.2 mg/kg, IV) was administered to maintain a central eye position. The mass and a free margin were removed by full-thickness corneoscleral resection. A corneoscleral graft was harvested from a dog that had been euthanised for reasons unrelated to this study and sutured with 9-0 polyglactin 910 using a simple interrupted pattern. The mass was immediately fixed in 10% neutral buffered formalin and submitted for histological sectioning and routine staining. Based on the histopathological analysis it was confirmed limbal melanocytoma. Postoperative treatment consisted of topical administration of 0.3% flurbiprofen every 6 h for 15 days, and a combination of topical ciprofloxacin/dexamethasone eye drops every 6 h for 30 days. Systemic carprofen (4 mg/kg per day, VO) was prescribed for 10 days. Topical tropicamide was used twice daily for 1 week. Cyclosporin 0.2% eye drops were applied twice daily for 2 months. Examination of the left eye two months after surgery revealed decreased corneal vascularization, and the results of pupillary light response and vision testing were normal. The values of intraocular pressure remained normal in all postoperativeevaluations. The patient was followed for 36 months postoperatively, during which time there was no recurrence.Discussion: Limbal melanomas are the most common ocular melanomas in dogs. Most of them develop slowly and are located closely to the superior limbus. The tumors tend to grow more rapidly in younger dogs and more slowly in older dogs. Labrador Retrievers and German shepherds appear to be affected more frequently than other breeds. The present case involved a 5-year-old Labrador breed. The clinical presentation included a pigmented limbal mass extending into the adjacent cornea, sclera and conjunctival tissue. A tissue biopsy is necessary to confirm the diagnosis. In the present case, the diagnosis of limbal melanocytoma was based on clinical signs and confirmed by histopathological examination. The choice of treatment is influenced by the tumour size and location, availability of equipment and materials, clinician expertise and the cost of treatment. Some techniques for removing the mass and repairing the resultant corneoscleral defect has been described. In the present case, due to the location and size of the mass and the absence of intraocular invasion, surgical removal including a margin of normal tissue was performed. With this surgical procedure, the intention was to preserve the eyeball and maintain vision. In this case, surgical excision of a limbal melanocytoma combined with homologous corneoscleral graft was effective for repairing a full-thickness corneoscleral defect and preserving ocular function.